Respuesta :
Answer:
Infinitely many solutions.
Step-by-step explanation:
-t=9(t-10)-t=9(t-10)
-t=9t-90-t=9t-90
-t=8t-90=9t-90
8t-(-t)-90=9t-90
8t+t-90=9t-90
9t-90=9t-90
Answer:
If you mean −t=9(t−10), then the answer is 9, if you mean −t=9(t−10)−t=9(t−10) then infinite solutions.
Step-by-step explanation:
Here is the answer if you mean −t=9(t−10):
−t = 9 (t−10)
Simplify the equation.
-t = (9)(t) + (9)(-10)
-t = 9t + -90 (Add the opposite)
-t = 9t - 90
Subtract -9t
-t -9t = 9t - 90 - 9t
-10t = - 90
Divide -10 on both sides to make sure the equation is balanced on both sides. And to isolate t to get the final answer.
-10t = -90
-10t = -10
Therefore,
t = 9
Is the final answer.
I Hope this helps! Have a great rest of your morning, afternoon, or evening! :D